Peningkatan Pengetahuan Perawatan Kesehatan Gigi dan Mulut Melalui Penyuluhan dan Praktik Sikat Gigi pada Anak di Kelurahan Bandarharjo Kota Semarang - Agnes Dwi Safarina; Nirmala Al Fatiah; Nabila Azzahra Luthfiah; Kirana Rannoe Tirta; Adhisti Lutfia Hanan; Ari Yuniastuti (Jurnal Pengabdian Masyarakat Dharma Andalas, 2022)
The high number of stunting children in Bandarharjo Village, North Semarang, Semarang City is a chronic health problem, one of which causes oral health problems. One of the efforts to prevent stunting in children is to provide counseling and practices to maintain and care for dental and oral health. UNNES Giat's work program is to provide education to children aged 6-12 years to be able to maintain and care for dental and oral health. The result of this activity is that the children know both theoretically and practically about choosing the right brush and toothpaste and the correct way to brush their teeth.